2004
DOI: 10.1074/jbc.m404599200
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP-Epac-Rap1 Pathway Regulates Cell Spreading and Cell Adhesion to Laminin-5 through the α3β1 Integrin but Not the α6β4 Integrin

Abstract: Laminin-5 is an important constituent of the basal lamina. The receptors for laminin-5, the integrins ␣ 3 ␤ 1 and ␣ 6 ␤ 4 , have been associated with epithelial wound migration and carcinoma invasion. The signal transduction mechanisms that regulate these integrins are not well understood. We report here that the small GTPase Rap1 regulates the adhesion of a number of cell lines to various extracellular matrix proteins including laminin-5. cAMP also mediates cell adhesion and spreading on laminin-5, a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 56 publications
4
88
0
3
Order By: Relevance
“…Furthermore, Rap1B has been shown to play a critical role in axon specification in hippocampal neurons (Schwamborn and Puschel, 2004). A role for Rap1 in growth cone spreading has not been previously reported, but is consistent with the known role of Rap1 in promoting integrin-mediated adhesion, actin polymerization, and cell spreading (Ohba et al, 2001;Stork, 2003;Enserink et al, 2004;Bos, 2005). Our data suggest that Rap1 inactivation decreases integrin-mediated adhesion downstream of EphA4 in neuronal cells.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, Rap1B has been shown to play a critical role in axon specification in hippocampal neurons (Schwamborn and Puschel, 2004). A role for Rap1 in growth cone spreading has not been previously reported, but is consistent with the known role of Rap1 in promoting integrin-mediated adhesion, actin polymerization, and cell spreading (Ohba et al, 2001;Stork, 2003;Enserink et al, 2004;Bos, 2005). Our data suggest that Rap1 inactivation decreases integrin-mediated adhesion downstream of EphA4 in neuronal cells.…”
Section: Discussionsupporting
confidence: 75%
“…Integrins that specifically associate with actin seem to be regulated by Rap1, but not those that associate with intermediate filaments Enserink et al, 2004;Bos, 2005). The mechanism underlying these interactions is not completely understood, but Rap1-GTP-interacting adaptor molecule has been shown to play a critical role in linking Rap1 to integrins (Lafuente et al, 2004).…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…There is emerging evidence that stress hormones may modulate tumor-stroma interactions. For example, Enserink and associates have shown that the β-agonist isoproterenol promotes ovarian cancer cell spreading and adhesions via integrins through the Epac (exchange factor directly activated by cAMP)-Rap1 pathway [38,39]. Ultimately, stress hormones may promote cell-matrix attachment of cancer cells.…”
Section: Adhesionmentioning
confidence: 99%